Impact of an interprofessional oral health education program on health care professional and practice behaviors: a RE-AIM analysis - Braun PA; Widmer Racich K; Ling SB; Ellison MC; Savoie K; Reiner L; Westfall JM (Dove Medical Press, 2015)
Patricia A Braun,1 Katina Widmer Racich,1 Sarah B Ling,2 Misoo C Ellison,3 Karen Savoie,4 Linda Reiner,5 John M Westfall41University of Colorado Anschutz Medical Campus, Aurora, CO, USA; 2Department of Family Medicine, Broadlawns Medical Center, Des Moines, IA, USA; 3Colorado School of Public Health, Aurora, CO, USA; 4Area Health Education Center, University of Colorado Anschutz Medical Campus, Aurora, CO, USA; 5Caring for Colorado Foundation, Denver, CO, USA Background: Early childhood caries is the most common chronic childhood condition and largely preventable. Access to oral health preventive services (OHPS) for children at risk for caries is suboptimal and could be expanded if they were provided by non-dental professionals. Many state Medicaid programs in the USA now reimburse non-dental professionals for OHPS but require that they receive oral health education (OHE) to be reimbursed. Few OHE programs have been evaluated. Methods: We evaluated the impact of Colorado's OHE program on professional- and practice-level behaviors regarding the provision of OHPS to children by measuring its reach, effectiveness, adoption, implementation, and maintenance (ie, using the Reach Effectiveness Adoption Implementation Maintenance [RE-AIM] framework) with Medicaid claims data, online surveys, and key informant interviews. Results: From 2009 to 2012, the proportion of young, low-income children receiving OHPS from a medical professional increased 16-fold. We surveyed 703 OHE participants; post-OHE response rates were 61% at 12 months, 34% at 24 months (2009 participants), and 39% at 12 months (2011 participants). Respondents reported confidence in providing OHPS; favorable oral health knowledge, attitudes, and beliefs; and were providing OHPS to most eligible children. Approximately half of the practices had initiated practice-level changes to support program implementation and maintenance. Few barriers were reported to care. Eighteen interviewees reported factors facilitating program diffusion, which included quality materials, community need, and reimbursement; barriers included lack of time to provide services, resources to purchase supplies, and referral dentists. Conclusion: This evaluation of a state interprofessional OHE program shows evidence of program diffusion and identifies facilitating factors and barriers to having medical professionals provide OHPS.Keywords: oral health, health services, interprofessional education, child health services, primary prevention, oral health preventive services